Big book of who. Women in sports : the 101 athletes every fan needs to know. (Chicago, Illinois : Triumph Books LLC, 2024)
Presents 101 star athletes, both past and present, in baseball, basketball, football, golf, hockey, Olympics, racing, soccer, tennis, and extreme sports.
Superstars -- Wonder women -- Trailblazers -- Record breakers -- Champions.
Includes index.
3-6
Keywords: Women athletes -- Juvenile literature; Professional athletes -- Juvenile literature; Sports -- Juvenile literature; Women athletes; Professional athletes; Sports